Öğretmen Algılarına Göre Fark Oluşturan Öğretmen - Abdullah Çetin; Serkan Ünsal (İnsan & Toplum)
"is research aimed to explore the characteristics of the teachers who make a difference along with the activities they did, the actions they took and the contributions they made to society. Having a qualitative research design, this research utilized a phenomenological design. "e working group of the research consisted of 12 volunteer teachers who completed their master degree at the department of Educational Sciences in Kahramanmaraş Sütçü İmam University during the 2018-2019 academic year and who had teaching experience. "e research employed semi-structured interview form prepared by the researchers. Content analysis was used during data analysis. "e teachers making a difference were found to differ from their colleagues with these characteristics such as taking responsibility in the solution of the social problems, producing practical solutions to problems, being open to criticism, having a unique personality. "e teachers were determined to make a difference by doing social activities, solving social problems, guiding the society and bringing innovation. Besides, they demonstrated some behaviours like breaking out of the routine and not following the procedures. Various recommendations were provided in order to raise teachers who make a difference. Formal procedures should be reduced and free/democratic environment should be created during in-service training, while teachers should be speci$cally selected for the profession and faculty members should be role models during pre-service training. "e teachers who make a difference contributed to the social integrity, development, meeting the needs of the society, bringing individuals into society and making individuals gain values.